Critical success factors and their influence in ERP implementation success of organizational performance - Hassan, Marina; A. Jabar, Marzanah; Sidi, Fatimah; Jusoh, Yusmadi Yah; Abdullah, Salfarina (Zibeline International Publishing, 2018)
Effectiveness and efficiency of ERP execution is depending on the organization implementation. Every company that embarks on ERP execution will definitely hope that the execution will be success and effective. The concept of Critical Success Factors (CSFs) early emerged in 1961. Many studies have been conducted in order to analyze on the most CSFs. Few only intended di-rectly to focus on organizational performance. A conceptual model will be developing to show the relationship between all the selected CSFs towards organizational performance in making sure the successful of ERP implementation in the organization. Systematic Literature Review (SLR) has been done in order to gain the CSFs. Completely target CSFs will be list out and traceability matrix table will be produce due to the priority of organizational performance. Pilot study has been conducting to proof the conceptual model suggest. A questionnaire has been distributed to 30 industry respondents. Results from this questionnaire survey than will demonstrate either the CSFs is really effect the successful execution of ERP in organizational performance or need to do changes based on the outcome. This paper proposes specific CSFs that influence directly to ERP execution success towards organizational performance. These will be very useful to organization in order to check on the organizational performance towards the successful implementation of ERP.